TRENDS IN PLACE OF DEATH, AND THE EFFECT OF DEATH CERTIFICATE CLASSIFICATION AND CODING CHANGES, IN PARKINSONS DISEASE, MOTOR NEURONE DISEASE, AND MULTIPLE SCLEROSIS IN ENGLAND: 1993–2010. (29th November 2012) - Sleeman, K; Ho, YK; Verne, J; Glickman, M; Silber, E; Gao, W; Higginson, IJ
Abstract : Background: Mortality statistics are ideal for studying national trends in place of death, but the impact of changes over time in classification and coding is not fully understood. Aim: To determine place of death in Parkinsons disease (PD), motor neurone disease (MND) and multiple sclerosis (MS) in England, 1993–2010. To examine the effect on this of classification and coding changes, and of using underlying cause compared to any mention. Methods: All deaths in England from 1993–2010 with a mention of PD, MS or MND were identified from ONS mortality data. ORs of place of death for deaths coded with PD, MS or MND as underlying cause, compared to all other underlying causes, were calculated. Results: Underlying causes of PD and MS increased care home death (OR 1.63, 1.58–1.68 and 1.62, 1.48–1.77), and reduced hospice (OR 0.39, 0.32–0.46 and 0.55, 0.45–0.68) and hospital (OR 0.64, 0.62–0.66 and 0.74, 0.69–0.79) death. An underlying cause of MND increased hospice (OR 5.34, 4.02–7.09) and home (OR 1.82, 1.61–2.06) death, and reduced hospital death (OR 0.48, 0.44–0.53). Pre-2001, deaths coded as underlying cause pneumonia were more likely to occur in hospital in all three conditions. Discussion: Place of death varies according to neurological condition, and by underlying cause of death. Further analyses of factors affecting place of death should focus on the underlying cause of death. Changes over time in classification and coding should be taken into account in such analyses.